Pendidikan Keluarga Dalam Perspektif Hadits Nabi - Muslim Muslim (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
The family is the first place as well as the first institution in education which is often referred to as an informal institution. In the Sisdiknas (national education system) law, it is stated that “informal education is the path of family and environmental education.” On this basis, it is constitutionally proven that the existence of an informal educational path or also known as an educational path in the family becomes a formal legal force.